(untitled) (Revista Sistemas de Producción Agroecológicos, 2017)
The diseases in rice (Oryza sativa) are one of the main constraints of their productivity causing instability in the yield of this cereal, therefore a good fertilization system is recommended. The objective of the present study was to evaluate two rice varieties: Fedearroz 68 (VF 68) and Victoria 10-39 (VV10-39) performed in Villavicencio (Meta); the varieties were planted an area of 1080 m2, with certified seed, making weed control, pests and diseases according to the degree of infestation that was presented. The fertilization began 15 days after sowing, subsequently was fertilized every 15 days Up to complete a total of three or four applications. The treatments (T) were: 1= 45% organic with carbon; 2= 90% organic without carbon; 3= 100% chemical with urea (traditional); 4= 100% chemical without urea (another traditional alternative); 5= 45% organic with DAP (P2O5) and 6= 90% organic without DAP. FO1= organic fertilizer 1 (organic N); FO2= organic fertilizer 2 (N ureic); FQ1= chemical fertilizer 1 (boron); FQ2= chemical fertilizer 2 (urea); FQ3= chemical fertilizer 3 (DAP); FQ4= chemical fertilizer 4 (carbon); FQ5= chemical fertilizer 5 (potassium chloride); and FQ6 = chemical fertilizer 6 triple 15 (15N 15K2O and 15P2O5). For the collection of samples frames of 2x3 (6 m2) were built to locate the two varieties in all test blocks; the panicles were cut to determine grain weight, in addition, 10 panicles were collected per block to evaluate full and weighted grain weight, to evaluate the weight of the full and banned grain, and with it estimate percentage of banishing and stained in grain, also the incidence rate of the following pathogens was estimated: Sarocladium oryzae, Helminthosporium, Ácaros, Gaenomices, Pyricularia oryzae and white-leaf virus (WLV). The performance components that were analyzed provided data that allow the conclusion that fertilization with T4 in VV 10-68 is best nutritional contribution gave the plant, generating an optimal development of the crop, allowing it to be the treatment with greater tolerance to the phytosanitary problems that arose, while in T1 the fertilization was not enough to generate a good nutrition and thus meet the phytosanitary problems, in addition its physiological development was delayed and weak. In VF 68 the T5 showed the best results in all variables evaluated, while T6 was the lowest performing and was susceptible to most phytosanitary problems.